Multiple effects of Mg1-xNixO coating on P2-type Na0.67Ni0.33Mn0.67O2 to generate highly stable cathodes for sodium-ion batteries - Kim, Hyeongwoo; Park, Jae-Ho; Kim, Sung-Chul; Byun, Dongjin; Chung, Kyung Yoon; Kim, Hyung-Seok; Choi, Wonchang (ELSEVIER SCIENCE SA, 2021)
P2-type Na0.67Ni0.33Mn0.67O2 (NNMO) is a state-of-the-art, high-energy and high-voltage cathode material in sodium-ion batteries. However, surface degradation effects, such as P2-O2 phase transformation, ordering of Na+/vacancy, electrolyte decomposition, and HF attack, limit its electrochemical stability. To counter these effects, we applied Mg1-xNixO (MgNiO) as a coating formed via wet-chemical coating to suppress unfavorable side reactions; surface doping of Mg2+ also occurs post-calcination, which is expected to reduce P2-O2 transition near the surface structure. MgNiO-NNMO exhibited outstanding cycling stability (70.08 mAh g(-1) over 200 cycles) and rate capability (39.41 mAh g(-1) at 5C over 800 cycles). The influence of Mg2+ doping was studied comprehensively through in situ and ex situ X-ray diffraction analysis. Furthermore, to characterize the protective role of the MgNiO coating in harsh conditions, we operated NNMO as Na half cells at a high temperature of 60 degrees C and high voltage of 4.5 V (vs. Na+/Na) for the first time; under these conditions, MgNiO-NNMO exhibited remarkable cycling stability (52.68 mAh g(-1) over 100 cycles) as compared to pristine NNMO (7.213 mAh g(-1) over 100 cycles). Surface analysis via X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectroscopy were also conducted to investigate the impact of electrolyte decomposition and HF attack. (C) 2020 Elsevier B.V. All rights reserved.